Integrated nutrient management options for soybean (Glycine max L., Merrill) varieties for higher productivity, quality and profitability under west-central plains of India - Singh, Rakesh; Sharma, H.B.; Kumar, Parveen; Paliwal, Dinesh Kumar (Annals of Agricultural Research, 2016)
Integrated nutrient management has become very important due to deteriorating soil health specially decline in organic carbon content in the west-central plains of India. A field experiment was conducted during 2009 and 2010 on sandy-loam soil. Three cultivars of soybean (JS-93-05; PK-472; NRC-37) were sown with six nutrient management options. The results indicated that maximum value of seed yield (2.90 t/ha) and protein yield (1134.6 kg/ha) were recorded with treatment 15-30-20 kg/ ha N:P2O5:K2O + poultry manure @ 5 t/ha. Though, maximum yield of oil (552.1 kg/ha) was recorded in treatment 60-60-40 kg/ha N:P2O5:K2O where 200% N was applied along with recommended dose of P and K, but it was very close and statistically at par with treatment 15-30-20 kg/ha N:P2O5:K2O + poultry manure @ 5 t/ha (551.7 kg/ha). Maximum net returns (Rs.35,761) and benefit cost ratio (2.56) were also recorded in treatment 60-60-40 kg/ha N:P2O5:K2O, which was statistically similar with treatment 15-30-20 kg/ha N:P2O5:K2O + poultry manure @ 5 t/ha (Rs. 34,810 and 2.43, respectively). Across the nutrients management options maximum, seed yield (2.72 t/ha), oil yield (523.8 kg/ha) protein yield (1065.1 kg/ha), net returns (Rs.33,387) and benefit cost ratio (2.47) were recorded in cultivar JS 93-05 while, lowest values for above stated variables were observed in cultivar PK 472.